Hourly Work of 3D Microstructural Visualization of Dual Phase Steels by SliceGAN. Issue 7 (15th April 2022) - Sugiura, Keiya; Ogawa, Toshio; Adachi, Yoshitaka
Abstract: SliceGAN is used to generate a 3D microstructure image from one or three 2D images in ferrite‐martensite dual phase steels. This method accelerates 3D visualization of microstructure to be hourly task. The 2D images sliced from the SliceGAN‐3D image seem to be quite similar with the original 2D images. The volume fraction of martensite in SliceGAN‐3D image is in good agreement with that in experimentally reconstructed 3D image. Abstract : SliceGAN‐generated three‐dimensional (3D) images for (a)DP1 and (b)DP2. Green and red phase correspond to martensite and ferrite, respectively